2008
DOI: 10.1177/0899764008314808
|View full text |Cite
|
Sign up to set email alerts
|

Is the Grass Greener? Sector Shifting and Choice of Sector by MPA and MBA Graduates

Abstract: Despite debate about distinctions among employment in the government, nonprofit, and business sectors, little research exists on the likelihood of, or barriers to, movement across sector boundaries. The authors propose and test models explaining individuals' current sector of employment-business, government, or nonprofit-and their sector-shifting behavior. They use survey data from 688 alumni of four schools: two offering MBAs and two offering MPAs. Study results indicate that most respondents have a favored s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
121
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 29 publications
16
121
3
Order By: Relevance
“…However, high levels of PSM are not found to be a predictor of public sector employment (Lewis & Frank, 2002). Other findings, for example, that of Tschirhart, Reed, Freeman and Anker (2008), support the idea that individuals having a preference for helping others (which is part of PSM) will selfselect into the public sector. But they do not find an effect of salary preferences in relation to sector preference.…”
Section: Application Of Behavioural Economics In Public Servicesupporting
confidence: 52%
“…However, high levels of PSM are not found to be a predictor of public sector employment (Lewis & Frank, 2002). Other findings, for example, that of Tschirhart, Reed, Freeman and Anker (2008), support the idea that individuals having a preference for helping others (which is part of PSM) will selfselect into the public sector. But they do not find an effect of salary preferences in relation to sector preference.…”
Section: Application Of Behavioural Economics In Public Servicesupporting
confidence: 52%
“…Nevertheless, consistent with an increased emphasis in the literature on nonpecuniary job attributes as determinants of employee behavior, several studies investigate how intrinsic motivation influences individuals' decision to accept public sector employment. 3 Largely, these studies confirm that intrinsic motivation, or PSM, predicts individuals' desire to work in the public sector (Lewis and Frank 2002;Tschirhart et al 2008). For example, Lewis and Frank (2002) find that public sector employees have high levels of PSM, although its impact on choosing public sector employment is strongest for college graduates and teachers jobs than for public administration positions.…”
mentioning
confidence: 69%
“…Perry (1996) proxies PSM by survey questions focusing on attraction to policy making, commitment to public interest, compassion, and self-sacrifice. Crewson (1997), Lewis and Frank (2002), and Tschirhart et al (2008) use responses to a question on the importance of ''working in a job that allows one to help other people and a job that is useful to society,'' whereas Feeney (2008) uses responses to the question about the importance of ''. .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis and Frank (2002) showed that people for whom it is important to be "useful to society" and to "help others" are more likely to want to work for the government. In accordance with this, Tschirhart et al (2008) found that MBA and MPA students, who value to have "a career that allows them to help others", also have a preference to work in the public or nonprofit sector.…”
Section: Prosocial Attitudes Across Sectorsmentioning
confidence: 56%